DESIGN OF SECANT PILE WALL WITH GROUND ANCHOR AND BORED PILE FOUNDATION OF CREATIVE CENTER IN BINTARO JAYA - Chaira, Salsabila
The construction of the Creative Center in Bintaro Jaya, South Tangerang has the aim to empower creative economy businesses. The Creative Center in Bintaro Jaya Project is planned to have six floors of the upper structure and two floors of the basement structure. The basement are will be used as a parking lot for visitors and utility room. The lowest basement floor is at a depth of -7.8 m with a distance between basement floors of 4.2 m. Therefore, technical planning is needed in the geotechinical engineering, including the design of retaining walls and deep foundations. Basement excavation is carried out to a depth of -7.8 m. The type of retaining wall for basement excavation construction to resist lateral soils load is a secant pile with a diameter of 0.8 m and penetration depth of 16 m. The secant piles are strengthened with two layers of ground anchors at a depth of -1 m and -5 m. The modelling of secant pile and ground anchor is analyzed by PLAXIS 2D software. In addition, the design of dewatering due to seepage and rainwater will use a passive dewatering method with a u-ditch and sumpt pit. The bored pile foundation is designed with a diameter of 1 m with a depth of 16 m and 1.2 m with a depth of 18 m. The bearing capacity of single pile and pile groups are analyzed by LPILE and GROUP software.